2018
DOI: 10.3892/etm.2018.6893
|View full text |Cite
|
Sign up to set email alerts
|

Arterial blood gas and acid‑base balance in patients with pregnancy‑induced hypertension syndrome

Abstract: This study aimed to investigate the expression of arterial blood gas and acid-base balance in patients with pregnancy-induced hypertension syndrome and their influence on newborns. A total of 348 patients with pregnancy-induced hypertension syndrome (research group) admitted and treated in the First People's Hospital of Jining from March 2013 to March 2016 were retrospectively analyzed, and another 156 cases of healthy pregnant women who were physically examined were selected as the control group. Blood gas an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…The acid-base balance was examined by measuring the pH, base excess (BE), bicarbonate ion concentration (HCO 3 − ) [ 22 ], and blood lactate concentration (Lac) to assess the tissue hypoxia of rats together with the blood gas parameters. The pH in the HES200 group was increased significantly at 60 min compared with BL and H3 ( P < 0.01, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The acid-base balance was examined by measuring the pH, base excess (BE), bicarbonate ion concentration (HCO 3 − ) [ 22 ], and blood lactate concentration (Lac) to assess the tissue hypoxia of rats together with the blood gas parameters. The pH in the HES200 group was increased significantly at 60 min compared with BL and H3 ( P < 0.01, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…HDP is a special disease occurring during pregnancy, mainly characterized by edema, proteinuria, and hypertension (Hansson et al 2014). In severe cases, diffuse intravascular coagulation, placental abruption, heart failure, cerebral hemorrhage, coma, convulsion and even death may occur (Cao et al 2019). At present, the etiology and pathogenesis of HDP have not been clearly defined, and its diagnosis depends on clinical manifestations and laboratory indicators.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, our results had shown that uptake of pravastatin by OATP1A2 occurs at physiological pH in vitro, which suggests that this transporter could contribute to the placental uptake of pravastatin. Cao et al, 2019 reported a decrease of maternal arterial blood pH in cases of pregnancy-induced hypertension 47 ; and gestational hypertension can be complicated with preeclampsia in up to 50% of the affected women. 48 Thus, a shift in the pH microenvironment of the maternal-placental interface towards acidification in preeclampsia 49 can affect the activity of OATP1A2-mediated uptake of the drug, as the function of this transporter is sensitive to pH.…”
Section: Discussionmentioning
confidence: 99%